Heat‐killed Helicobacter pylori upregulates NKG2D ligands expression on gastric adenocarcinoma cells via Toll‐like receptor 4. Issue 4 (29th April 2021) - Hernández, Carolina; Toledo‐Stuardo, Karen; García‐González, Paulina; Garrido‐Tapia, Macarena; Kramm, Karina; Rodríguez‐Siza, José Alejandro; Hermoso, Marcela; Ribeiro, Carolina H.; Molina, María Carmen
Abstract: Background: Natural killer (NK) cells are paramount for immunity against infectious agents and tumors. Their cytokine and cytolytic responses can be mediated by natural killer group 2, member D (NKG2D), an activating receptor whose ligands (NKG2DL) expression is induced in conditions of cell stress and malignant transformation. Since sustained expression of NKG2DL MICA is related to lower survival rates in gastric adenocarcinoma patients, and Helicobacter pylori infection contributes to tumorigenesis; we asked whether H .  pylori stimulus could promote NKG2DL expression on human gastric adenocarcinoma cells. Methods: Heat‐killed H .  pylori (HKHP) was used to stimulate MKN45 cells before analysis of NKG2DL and Toll‐like receptor 4 (TLR4) protein levels by flow cytometry and transcripts by real‐time PCR. LPS from Rhodobacter sphaeroides and inhibitory peptide Pepinh MYD were used to inhibit TLR4/MyD88 signaling pathway to assess its participation on NKG2DL expression. NK cell‐mediated cytotoxicity was measured by lactate dehydrogenase (LDH) and CD107a mobilization assays. Results: Stimulation of MKN45 cells with HKHP increased MICA, ULBP4 (another NKG2DL), and TLR4 at the protein and transcriptional levels. MICA, but not ULBP4 expression, was upregulated in a TLR4/MyD88‐dependent manner. Furthermore, the presence of NKG2DL on the surface of HKHP‐stimulated MKN45 cells enabled NK cell cytotoxic activation. Conclusions: Our data indicate that induction of NKG2DL expression on gastric adenocarcinoma cells by H .  pylori promotes an immune response that may ultimately contribute to either gastric tissue damage, as a consequence of persistent activation of immunity, or tumor immune evasion due to chronic NKG2DL expression.